Incomplete Utterance Rewriting as Semantic Segmentation - LIU, Qian; Chen, Bei; Lou, Jian-Guang; ZHOU, Bin; Zhang, Dongmei (EMNLP'20 (full paper), 2020)
Recent years the task of incomplete utterance rewriting has raised a large attention. Previous works usually shape it as a machine translation task and employ sequence to sequence based architecture with copy mechanism. In this paper, we present a novel and extensive approach, which formulates it as a semantic segmentation task. Instead of generating from scratch, such a formulation introduces edit operations and shapes the problem as prediction of a word-level edit matrix. Benefiting from being able to capture both local and global information, our approach achieves state-of-the-art performance on several public datasets. Furthermore, our approach is four times faster than the standard approach in inference.